(3fXe GdOQQ hGdYbjGf aj HjGf TQa Hfj RjGfs - (3GdJfSj , eMeO Hf YHO Gddg Hf YHO GdLdjd, CHh YHO Gddg,J (B899 (3g` s
(3ChdgG (B:s
(3jHOC HGdHGH GdKGdK ai GdNUdI GdJi gi QhM NUGd Gdedc GdeMehOI s
(3BNQgG (B:s
(3JfJgi YfO PcQ GdTLGYI s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B238 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B222s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B241 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B341 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B456 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(483 (3O(B) s
Keywords: (3GdJGQjNs